2021
DOI: 10.3389/fonc.2021.737767
|View full text |Cite|
|
Sign up to set email alerts
|

Real-World Lenvatinib Versus Sorafenib in Patients With Advanced Hepatocellular Carcinoma: A Propensity Score Matching Analysis

Abstract: BackgroundLenvatinib is approved for patients with advanced hepatocellular carcinoma (HCC) due to its non-inferiority to sorafenib of overall survival (OR) in clinical trials. This study was to compare the effectiveness and safety of lenvatinib and sorafenib in the real world.MethodsWe retrospectively evaluated 338 patients with unresectable HCC who had undergone lenvatinib or sorafenib treatment between January 2018 and August 2020. Propensity-score matching analysis was performed with a 1:2 ratio to reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 25 publications
2
30
0
1
Order By: Relevance
“…Of the 24 studies included, one was a phase III randomized controlled trial (RCT) [ 8 ], and the other 23 were retrospective studies [ 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], involving 2438 patients with unresectable HCC who received first-line treatment with lenvatinib. The initial dose of oral lenvatinib was 12 mg QD for patients with a body weight of ≥60 kg, or 8 mg QD for those with a body weight of <60 kg.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 24 studies included, one was a phase III randomized controlled trial (RCT) [ 8 ], and the other 23 were retrospective studies [ 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], involving 2438 patients with unresectable HCC who received first-line treatment with lenvatinib. The initial dose of oral lenvatinib was 12 mg QD for patients with a body weight of ≥60 kg, or 8 mg QD for those with a body weight of <60 kg.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding clinical observations, in a randomized clinical trials comparing anti-cancer effectiveness it has been demonstrated that treatment of RR-DTC with lenvanitib was associated with a longer progression-free survival compared with sorafenib [ 8 , 28 ]. In case of treatment of HCC, lenvatinib showed comparable overall survival and progression-free survival but longer time to progression and better tumor response compared to sorafenib [ 29 , 30 ]. However, treatment of both, i.e., RR-DTC and HCC, with lenvatinib was associated with more frequently occurring severe adverse effects, especially hypertension and proteinuria [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In case of treatment of HCC, lenvatinib showed comparable overall survival and progression-free survival but longer time to progression and better tumor response compared to sorafenib [ 29 , 30 ]. However, treatment of both, i.e., RR-DTC and HCC, with lenvatinib was associated with more frequently occurring severe adverse effects, especially hypertension and proteinuria [ 28 , 29 , 30 ]. It should be noted that generally adverse events lead to dose reduction or discontinuation of treatment more frequently in cases of lenvatinib than ofsorafenib [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the cancer stage at the start of TKI therapy was lower in the lenvatinib group than in the sorafenib group. Recent real‐world clinical studies and propensity score matching analysis of aHCC comparing lenvatinib and sorafenib have shown that lenvatinib treatment is more effective 17–19 . In addition, the molecular‐targeted therapy is to start as early as possible for patients who are unsuitable for TACE, although chemotherapy has been formerly introduced only after repeated TACE 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent real‐world clinical studies and propensity score matching analysis of aHCC comparing lenvatinib and sorafenib have shown that lenvatinib treatment is more effective. 17 , 18 , 19 In addition, the molecular‐targeted therapy is to start as early as possible for patients who are unsuitable for TACE, although chemotherapy has been formerly introduced only after repeated TACE. 11 Changes in the position of chemotherapy for HCC over time may be a limitation to the present analysis.…”
Section: Discussionmentioning
confidence: 99%